2015
DOI: 10.1371/journal.pone.0125669
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Estimation of GFR Improves Prediction of Dialysis and Recovery after Kidney Transplantation

Abstract: BackgroundThe early prediction of delayed graft function (DGF) would facilitate patient management after kidney transplantation.MethodsIn a single-centre retrospective analysis, we investigated kinetic estimated GFR under non-steady-state conditions, KeGFR, in prediction of DGF. KeGFRsCr was calculated at 4h, 8h and 12h in 56 recipients of deceased donor kidneys from initial serum creatinine (sCr) concentrations, estimated creatinine production rate, volume of distribution, and the difference between consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 34 publications
2
62
0
1
Order By: Relevance
“…The Jelliffe equation for unstable kidney function, which is calculated on the basis of the volume of distribution and creatinine kinetics rather than steady state parameters such as body weight or age, correlated well with CCr in a small study of 12 patients in the ICU 33,34 . The kinetic eGFR, which similarly to the Jelliffe equation, estimates GFR on the basis of the creatinine kinetics has shown promise in renal transplant recipients, but should be validated in other cohorts such as hospitalized patients with native kidneys 35 . Iohexol clearance has been used in critically ill patients but as mentioned above, is laborious and time consuming 36,37 .…”
Section: Management Of Persistent Akimentioning
confidence: 99%
See 1 more Smart Citation
“…The Jelliffe equation for unstable kidney function, which is calculated on the basis of the volume of distribution and creatinine kinetics rather than steady state parameters such as body weight or age, correlated well with CCr in a small study of 12 patients in the ICU 33,34 . The kinetic eGFR, which similarly to the Jelliffe equation, estimates GFR on the basis of the creatinine kinetics has shown promise in renal transplant recipients, but should be validated in other cohorts such as hospitalized patients with native kidneys 35 . Iohexol clearance has been used in critically ill patients but as mentioned above, is laborious and time consuming 36,37 .…”
Section: Management Of Persistent Akimentioning
confidence: 99%
“…Alternative or complementary measures of kidney function, including other filtration markers such as cystatin C and timed urine clearance measurements, could hold promise for improved phenotyping of functional recovery from AKD but require further validation before recommending their routine adoption into clinical practice 35,[63][64][65][66] . Methods to assess glomerular functional reserve (for example, by assessing the effect of a protein load on GFR) or tubular functional reserve (for example, through furosemide stress testing or the administration of intravenous creatinine) have also been developed in the CKD setting but have yet to be applied to patients with AKD 67,68 .…”
Section: Consensus Statement 2hmentioning
confidence: 99%
“…Approximately 20-30% of deceased donor kidneys and half the kidneys donated after cardiac death develop delayed graft function (DGF) [1]. DGF is usually defined as a requirement for dialysis within 1 week after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…[5]). The KeGFR formula is potentially adaptable to other filtration biomarkers including plasma cystatin C [1]. Also intuitive is the suggestion that if the rate of excretion (E) is less than the rate of production (estimated generation, eG) of creatinine, then the ratio (E/eG) would be a near ‘real-time' marker of kidney performance [6] relative to steady state performance, and therefore a predictor of DGF.…”
Section: Introductionmentioning
confidence: 99%
“…However, 2 recently published articles reported that kinetic GFR improved risk prediction in a clinical model of delayed graft function. 8,9 Other researchers have shown that, in cardiac surgery patients, kinetic GFR modeling enabled the early identification of patients with AKI before significant incremental increases in serum creatinine appeared. 10 Our results showed the superiority of kinetic GFR estimation to MDRD and CG GFR estimation for predicting stages of AKI according to the RIFLE criteria, when creatinine-defined AKI staging is used.…”
Section: Discussionmentioning
confidence: 99%